Analisis Strategi Pemasaran Kamar Hotel Di Qunci Villas Hotel Lombok - Nicko Gana Saputra; Reni Sulistyowati; Raehanun (Politeknik Sahid, 2020)
Lombok is one of the tourism destinations that is quite attractive to domestic and foreign tourists. It causes the competition of the tourism world in Lombok getting tougher. one of them is hospitality business. To deal with the competition, of course the hotel needs a strategy in marketing its products, especially rooms which are the main products of the hotel. As well as the Qunci villas in Lombok hotels in determining the right marketing strategy, an analysis is certainly needed. This study was tested using SWOT analysis by identifying internal and external factors of the hotel, namely analysis of internal factors (strengths and weaknesses) and external factors (opportunities and threats) then formulated into External Internal Matrices, Cartesian Diagrams, and Swot Matrix. From the results of the analysis carried out on the Cartesian diagram, the Qunci villas position of the hotel is located in quadrant II which is a diversification position, wich mean even Qunci villas hotel lombok despite facing many threats it have the power to deal with these threats. In this case Qunci Villas has several alternative strategies, such as SO, ST, WO, and WT. with one selected strategy it is the ST strategy. ST's strategy that is suitable for Qunci Villas Hotel is to increase the expenditure of new lodging packages and promo packages that have never been held before, as well as adding and modifying products and facilities, then maximizing the use of technology owned by the hotel to expand the target market, thereby increasing occupancy and income at Qunci Villas Hotel Lombok.